P-096 The Influence of Affective Spectrum Disorders on Symptom Burden within Inflammatory Bowel Disease Populations. (February 2017) - Coates, Matthew; Gorrepati Venkata, Subhash; Navabi, Seyedehsan; Stuart, August; Bobb, Anne; Koltun, Walter; Tinsley, Andrew; Williams, Emmanuelle
Abstract : Background: Patients with inflammatory bowel disease (IBD), including both ulcerative colitis (UC) and Crohn's disease (CD), are likely to develop a wide variety of problematic symptoms. The symptom burden, or patient-reported number, frequency and severity of these issues, has a significant bearing on patient quality of life, healthcare resource utilization and choice of management options. Affective spectrum disorders (ASD), including anxiety and depression, may be either a cause or consequence of increased symptom burden. How these factors relate to disease activity together in IBD is less clear. The aim of this study was to investigate the relationship between symptom burden and ASD in IBD and to determine how disease activity influences this interaction. Methods: We performed a retrospective analysis using a consented IBD natural history registry between January 1, 2015 and June 30, 2016 from a single tertiary care referral center. Presence of anxiety or depression was determined from responses to the Hospital Anxiety and Depression Scale (HADS) (8 or greater indicating clinically significant scores). Demographics, labs, physician global assessment (PGA), endoscopic severity, total and sub-scores for validated surveys assessing severity (Harvey Bradshaw Index, Simple Clinical Colitis Activity Index) and frequency (Short Inflammatory Bowel Disease Questionnaire) of common IBD-related symptoms were also abstracted. Results: Two hundred sixty-two IBD patients (130f:132 m) were included in this study. Eighty-six had UC (32.8%; 40f:46 m), 163 had CD (62.2%, 83f:80 m) and 13 had indeterminate colitis (5.0%, 7f:6 m). One hundred twenty-one patients (46.1%) were found to have clinically significant anxiety and/or depression scores. Every symptom evaluated was significantly more common in IBD patients with ASD compared to those without, including fatigue (88.1% versus 48.6%, P < 0.0001), abdominal pain intensity and frequency (62.3% versus 29.9%, P < 0.0001), excess gas (44.9% versus 16.0%, P < 0.0001), fecal urgency (47.5% versus 14.5%, P < 0.0001), diarrhea (57.6% versus 33.3%, P < 0.0001), blood in stool (41.5% versus 20.1%, P < 0.001), nocturnal stooling (46.2% versus 32.6%, P < 0.05) and difficulty maintaining weight (55.9% versus 29.1%). IBD patients with ASD were also more likely to report the most severe level of fatigue ( P < 0.0001), abdominal pain ( P < 0.001), fecal urgency ( P < 0.001) and blood in their stool ( P < 0.05). These trends were also demonstrated in the UC and CD subpopulations. We found very weak strength of associations (r 2 = 0.09 or less) between the symptoms described above when correlated with any measure of inflammatory activity (including PGA, endoscopic inflammatory score, CRP and ESR). IBD patients with ASD did have significantly higher mean PGA, endoscopic inflammatory, CRP and ESR levels ( P < 0.05). However, ASD were not associated with worse inflammatory activity in patients with the most severe symptoms. Conclusions: IBD patients with anxiety and/or depression report more severe, frequent and types of symptoms than their counterparts without these disorders. Interestingly, although our analysis supported a relationship between ASD and inflammation, there was no significant difference in disease activity between those with and without ASD who reported the most severe symptoms. We also did not see a strong association between IBD inflammatory activity and reported symptom severity. These findings suggest that patient-reported symptoms are poor predictors of actual IBD activity and that ASD (dissociated from inflammation) may drive much of the symptom burden in IBD patients.